Bird News - December 2021 (Avocetta, 2021)
This column aims to collect a series of interesting observations and to make it accessible to the scientific community in future. We collect observations without time, space or species limitation but we focus on a limited series of category of interest. See more on Avocetta website: https://www.avocetta.org/bird-news-column/